Response of the Quasi‐Biennial Oscillation to Historical Volcanic Eruptions. Issue 20 (16th October 2021) - DallaSanta, K.; Orbe, C.; Rind, D.; Nazarenko, L.; Jonas, J.
Abstract: The impact of volcanic eruptions on surface climate is well‐appreciated, but their in situ impact on the Quasi‐Biennial Oscillation (QBO) has received comparatively little attention. This study examines the QBO responses to Krakatoa and Pinatubo using five configurations of the NASA Goddard Institute for Space Studies Model E2.2 and MERRA‐2 reanalysis. A dynamically consistent response is found in terms of static stability, zonal wind, and upwelling. Eruptions are found to bias the QBO towards a westerly state, such that the QBO period response depends upon the phase at the time of eruption. The QBO does not have a clear amplitude response to an eruption, based on these simulations. The underlying mechanisms appear not to be influenced to first‐order by interactive composition, sea surface temperatures, or long‐term trends in CO 2 and ozone‐depleting substances. Plain Language Summary: In the tropical stratosphere, the winds alternate between easterly and westerly, taking about 28 months to return to their original state. This "Quasi‐Biennial Oscillation" (QBO) is ordinarily quite stable, but it can be disturbed by large forcings such as geoengineering and volcanic eruptions. In this study, we consider two volcanic eruptions in the historical record—Krakatoa (1883) and Pinatubo (1991)—and their subsequent effect on the QBO. We simulate them using a climate model, and find that the QBO prefers a westerly state after eruptions. This is important because the QBO state affects surface climate and weather prediction. Our results are largely consistent with observations of Pinatubo, and they can be tested in other climate models. Key Points: Historical simulations of Krakatoa and Pinatubo are studied using the high‐top NASA GISS Model E2.2 Eruptions bias the Quasi‐Biennial Oscillation (QBO) towards a westerly state, and the period response depends on initial phase The signature of eruptions on QBO amplitude is unclear from these simulations alone